The Role of the Social Services, Women's Empowerment, and Child Protection Agency in Handling Cases of Child Abuse - Rusli, Tami; Purnama, M Rangga; Marantika, Chinthia Dita; Ramadhan, Muhammad Daffa Rizky (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses the function and authority of the Social Service for Women's Empowerment and Child Protection (Dinas Sosial P3A) in handling cases of violence against children in Bandar Lampung City. In the context of increasing sexual violence against children, the role of the Dinas Sosial P3A becomes very important, both in preventive efforts through socialization and education to the community, as well as repressive efforts through legal and psychological assistance for victims. This study uses a normative legal approach by examining various regulations, such as the Child Protection Law and Regional Regulations, as well as technical and managerial obstacles faced in their implementation. The results of the study show that legal protection for children has been regulated in various legal instruments that require synergy between local governments, law enforcement agencies, and civil society. This study emphasizes that institutional strengthening and increasing human resource capacity are key to creating an effective, responsive, and sustainable child protection system.